Customer Perception of Electronic Service Quality - Comparative Study in Indian Banking Sector - Bakshi, Arup Kumar; Parido, Bivraj Bhusan (Gyan Management Journal, 2012)
Bank service automation is a relatively new phenomenon in India in the post-reform phase technology integration with banking service operations emerged as a critical quality dimensi public sector, private and foreign banks operating in India. Access to technology and the rate & ti adoption of the same may prove to a differentiating factor in gaining competitive advantage exploratory study investigates customers'· perception of electronic banking service quali comparing the same offered by State Bank of India and AXIS bank Modified E-SERVQUAL technique developed by Zeithaml eta/ {1992) to assess electronic service quality was used for the with a number of statistical analytical processes for testing the hypotheses developed. The revealed significant differences in the perceived electronic service quality of the respon representing the two banks reflecting major issues that may be addressed by the banks in near fe The study has geographical constraints and variable limits.
Keywords: Automation; electronic; service quality; perception; comparative; Bank